The internal pH of the forespore compartment of Bacillus megaterium decreases by about 1 pH unit during sporulation. - Magill, N G (1994)
Previous work has shown that the internal pH of dormant spores of Bacillus species is more than 1 pH U below that of growing cells but rises to that of growing cells in the first minutes of spore germination. In the present work the internal pH of the whole Bacillus megaterium sporangium was measured by the distribution of the weak base methylamine and was found to decrease by approximately 0.4 during sporulation. By using fluorescence ratio image analysis with a fluorescein derivative, 2',7'-bis(2-carboxyethyl)-5 (and -6)-carboxyfluorescein (BCECF), whose fluorescence is pH sensitive, the internal pH of the mother cell was found to remain constant during sporulation at a value of 8.1, similar to that in the vegetative cell. Whereas the internal pH of the forespore was initially approximately 8.1, this value fell to approximately 7.0 approximately 90 min before synthesis of dipicolinic acid and well before accumulation of the depot of 3-phosphoglyceric acid. The pH in the forespore compartment was brought to that of the mother cell by suspending sporulating cells in a pH 8 potassium phosphate buffer plus the ionophore nigericin to clamp the internal pH of the cells to that of the external medium. We suggest that at a minimum, acidification of the forespore may regulate the activity of phosphoglycerate mutase, which is the enzyme known to be regulated to allow 3-phosphoglyceric acid accumulation during sporulation.